Colour image segmentation of tuberculosis bacilli in Ziehl-Neelsen-stained tissue images using moving K-Mean clustering procedure - M. K. Osman; Mohd Yusoff, Mashor, Prof Madya Dr.; Z. Saad; H. Jaafar (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/